Punishment in the slammer: penal spectatorship among college students. - Hillgren, Casey J. (Kansas State University, 2011)
This thesis focuses on how citizens engage in the punishment of criminals in their everyday lives through means that seem neutral and largely invisible. It is at a distance that citizens are able to voyeuristically make sense of punishment, while using their position of privilege to engage in individualistic judgment. The consumption of punishment by everyday citizens is often experienced in a variety of forms, such as watching television, navigating the internet, playing video games, reading periodicals, and touring prisons. These experiences amount to a set of practices that tend to both exclude and punish. Each of these practices provide opportunities for the researcher interested in understanding penal spectatorship to observe the everyday consumption of punishment. The focus of this research project seeks to untangle the extent to which citizens engage in multiple forms of penal spectatorship in their everyday lives. One media form which encompasses aspects of the penal spectatorship theory is a mug shot newspaper called The Slammer. This project asks specific questions about The Slammer, in addition to more general questions about penal spectatorship. Specifically, I utilize content analysis to provide a descriptive context regarding the perceived gender and race among mug shots on the front cover of the magazine. Second, a survey was administered to 15,000 undergraduate students at Kansas State University for the purposes of measuring their exposure to mug shot newspapers, understanding of how citizens perceive the legitimacy of mug shot newspapers, their overall engagement in penal spectatorship avenues, whether the citizen feels punishment is justified and necessary for individuals who commit crimes, and finally citizen's opinions regarding the media portrayal of life in prisons and criminals and their crimes. In addition, the survey is comprised of three versions in order to conduct an experiment. Depending on the version of the survey, respondents were either given accurate, inaccurate, or no information pertaining to the mug shot individuals name and charged crime. The experiment seeks to measure respondents' perceptions of the individuals portrayed in The Slammer mug shots and the factors that may influence their perceptions. Furthermore, I work to develop composite indicators of key theoretical concepts developed among cultural criminologists. The results provide empirical evidence consistent with theorized overall growth in penal spectatorship.
Keywords: Penal spectatorship; Punishment; Media; Race; Gender; Sociology (0626)